Introduction of Indonesian Poem (Pantun) as a Creative Effort of Elementary School Students in Improving Language Skills in the Covid-19 Pandemic Era - Medani, Decky Ibrahim; Sakti, Asri Wibawa (Universitas Pendidikan Indonesia (UPI), 2022)
Learning activities are very impactful in the Covid-19 Pandemic Era so students are directed to study at home. Assistance from educators is very important to develop good literacy. With the Thematic Community Service Program, the purpose it is hoped that there will be an increase in student interest in learning and make it easier for educators and parents to carry out online learning activities. Including the introduction of Pantun in improving Language Skills in the Ciparay Hilir Region which is carried out online. The method in this study uses quantitative research. The results of this study are still many students who do not know the type of poem (known as pantun). Students' understanding of Pantun material, Types, and Language Skills by delivering material via PowerPoint or YouTube which is done online, and using the google meet application with educators. The results of the research show that the average post-test score of students is 70% greater than the average pre-test score of 37%, so the difference is 43%. Therefore, during the Covid-19 pandemic, there were still many efforts to increase literacy.